If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 1) + (x + 2) = 465 Reorder the terms: x + (1 + x) + (x + 2) = 465 Remove parenthesis around (1 + x) x + 1 + x + (x + 2) = 465 Reorder the terms: x + 1 + x + (2 + x) = 465 Remove parenthesis around (2 + x) x + 1 + x + 2 + x = 465 Reorder the terms: 1 + 2 + x + x + x = 465 Combine like terms: 1 + 2 = 3 3 + x + x + x = 465 Combine like terms: x + x = 2x 3 + 2x + x = 465 Combine like terms: 2x + x = 3x 3 + 3x = 465 Solving 3 + 3x = 465 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = 465 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 465 + -3 3x = 465 + -3 Combine like terms: 465 + -3 = 462 3x = 462 Divide each side by '3'. x = 154 Simplifying x = 154
| 9*72= | | y=4/3(18) | | (x+6)(x-3)(x-5)=0 | | (2x+6)(2x-3)= | | z-19=56 | | y=9/7(14) | | y=400+24x | | x^2-10y=40 | | 8*64= | | y=9/8(16) | | x^2-9=5(x-3) | | 2x+2(x+5)=310 | | 4x^2-17x+6=-8x+4 | | 3x-1-2x+1=6 | | 2x+4x=14-2 | | 6x-5=2x-7 | | 2/5s=18 | | 7-8n=4n-17 | | x^2+9x-5=7x+3 | | 7.95+n=10.10 | | -7(11+2y)-2y=-13 | | 17n+6=13n | | 6=10+x/4 | | 2y=5-1 | | x+(.5x)=3003 | | 5y=4-1 | | 8z+13=17 | | x+(x+2)=546 | | 12k+16k= | | 5y=2y+1 | | 12k+7=25k | | 5y=2+1 |